Permeation characteristics of fresh water in hollow fiber membrane module for pressure retarded osmosis - Shingo TERASHIMA (The Japan Society of Mechanical Engineers, 2016)
Pressure Retarded Osmosis (PRO) is expected to the new power generation system. The performance of the PRO module is closely relating to the permeation characteristics. In this paper, when fresh water flow rate is changed, 4 factors related to the reduction of permeation flow rate are researched with experiment. These 4 factors are concentration of solute in fresh water, salt leakage, concentration polarization, and dissipation of fresh water. The characteristics of the fresh water flow and permeation are studied for the hollow fiber membrane module used in PRO system. It is cleared that the dissipation of fresh water and the concentration polarization in hollow fiber largely influence to the reduction of permeation flow rate in the case of the low fresh water flow rate. Concentration of solute in fresh water, salt leakage influence to the reduction of permeation flow rate in the case of high fresh water flow rate.